Managing replication and transactions using neighbour replication on data grid - Noraziah Ahmad (Fakulti Sains dan Teknologi, 2011)
Replication is a useful technique for distributed database systems. Through this technique, a data object will be accessed (i.e., read and written) from multiple locations. Thus, it increases the data availability and accessibility to users despite site and communication failures. The all-data-to-all sites replication schemes such as Read-One-Write-All (ROWA) and Tree Quorum (TQ) are the popular techniques being used for replication and management of data in this domain. However, these techniques have its weaknesses in terms of data storage capacity and also data access times due to some number of sites must agree in common to execute certain transactions. In this study, the all-data-to-some sites scheme called Neighbour Replication on Grid (NRG) technique is proposed by considering only neighbours that have the replicated data. It is based on the logical structure of sites/servers in order to form a read or a write quorum in distributed database systems.